Near-infrared diffuse reflectance for quantitative and qualitative measurement of soluble solids and firmness of Delicious and Gala apples - Park, B; Abbott, J.A; Lee, K.J; Choi, C.H; Choi, K.H (Transactions of the ASAE, 2003)
Development of nondestructive measurements of soluble solids and firmness of apples benefits the producers, processors, and packers. The soluble solids and firmness (Magness-Taylor (MT) maximum force) of apples were predicted by diffuse reflectance measurement in the visible/near-infrared (400-1800 nm) regions of the spectrum. Two apple cultivars, Gala (n = 800) and Red Delicious (n = 960), were measured. The spectroscopic measurements of soluble solids and firmness for each apple were validated by a refractometer reading on the juice and a puncture test using a universal testing instrument, respectively. The soluble solids of apples could be predicted by NIR spectroscopic techniques with principal component regression (PCR) and Mahalanobis Distance (MD) analysis. The coefficients of determination (R2) for predicting soluble solids were 0.934 (SEP = 0.279; 10 factors) for Gala and 0.966 (SEP = 0.341; 10 factors) for Red Delicious apples with an NIR spectrum range (800-1100 nm). For classifying Gala apples into three classes based on the soluble solids, MD classifiers had classification accuracies of 93.5% for the full spectrum range (400-1800 nm) and 95.5% for the partial NIR spectrum range (800-1100 nm). Similarly, for the classification of Red Delicious apples, the classification accuracies were 92.1% with the full spectrum (400-1800 nm) and 93.6% with the partial NIR spectrum (800-1100 nm). A spectroscopic technique for apple firmness measurements was feasible for the Delicious apple. Using PCR models, the R2 values for predicting MT firmness were 0.218 (SEP = 4.91; 16 factors) for Gala and 0.786 (SEP = 7.02; 24 factors) for Red Delicious apples with the full spectrum (400-1800 nm), while the R2 values were only 0.291 (SEP = 4.92; 12 factors) for Gala and 0.657 for Red Delicious (SEP = 7.33; 24 factors) with the partial NIR spectrum (800-1100 nm). The MD analyses were also conducted to classify apples firmness. Based on three classes, the classification accuracies were 82.5% with the full spectrum (400-1800 nm) and 80% with the partial NIR spectrum (800-1100 nm) for Gala apples. Similarly, the classification accuracies were 83.8% with the full spectrum (400-1800 nm) and 75.3% with the partial NIR spectrum (800-1100 nm) for Red Delicious apples. This shows that spectroscopic techniques are feasible to classify apple firmness with over 80% accuracy.